Ten years of lesbian health survey research in the UK West Midlands - Sanderson Paul; Buckley Emily; Meads Catherine (BMC, 2007)
Abstract Background Very little is known about the physical health needs of lesbian and bisexual women in the UK; most research has looked at mental or sexual health only. This article reports the results of four surveys carried out in the West Midlands between 1995 and 2005. Methods The first two surveys were conducted in 1995-6 by a volunteer group, with participants from a lesbian health conference (n = 69) and in a convenience sample from a wide range of relevant groups and venues (n = 354). The second two surveys were commissioned by the West Midlands South Strategic Health Authority in partnership with the Gay Men's Health Network and were conducted in 2002 (n = 449) and 2005 (n = 166) and again used convenience sampling methods including the internet. Results The mean age of respondents varied between 29-33 years and 5-7% were from a non-white ethnic background. The smoking rates varied from 42% o 55%, being twice the West Midlands regional average of 21% for women aged 16 or more. Similarly, problems with alcohol were reported in 25-37% of respondents, higher than the West Midlands regional average of 7% for women aged 16+. The prevalence of any mental health problem varied between 31-35% and any suicide attempt between 20-31%. Only 29-45% had revealed their sexual orientation to their GP and of these, approximately 50% had experienced a positive reaction. Conclusion The results suggest health needs that current UK health services may not be meeting. There is a need to identify and target specific health measures for lesbians and bisexual women in order to ensure improved physical and mental health in the longer term.